Time-Varying Expected Small Firm Returns and Closed-End Fund Discounts - Swaminathan, Bhaskaran (Review of Financial Studies, 1996)
[This article describes the relation between closed-end fund discounts and time-varying expected excess returns on small firms. The results indicate that closed-end fund discounts forecast future excess returns on small firms. The information in discounts is independent of that in other commonly used forecasting variables such as the dividend yield on the market, the default spread, and the term spread. Furthermore, the closed-end fund discount forecasts only the small firm factor return and is the only variable that forecasts the small firm factor return. Additional tests indicate that the information in discounts is related to expectations of future earnings growth and expectations of future inflation. These results provide significant support for a rational explanation of the time-series relationship between discounts and expected returns on small firms.]